2008
DOI: 10.14411/eje.2008.061
|View full text |Cite
|
Sign up to set email alerts
|

Plant chemistry and aphid parasitoids (Hymenoptera: Braconidae): Imprinting and memory

Abstract: Abstract. Emerging parasitoids of aphids encounter secondary plant chemistry from cues left by the mother parasitoid at oviposition and from the plant-feeding of the host aphid. In practice, however, it is secondary plant chemistry on the surface of the aphid mummy which influences parasitoid olfactory behaviour. Offspring of Aphidius colemani reared on Myzus persicae on artificial diet did not distinguish between the odours of bean and cabbage, but showed a clear preference for cabbage odour if sinigrin had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…However, older larvae did not show this preference and attacked the two species of prey irrespective of the aphids that were previously fed. This is different from what has been shown for parasitoids (van Emden et al 2008 ) where the selectivity for prey can develop late during the larval -pupation phase and even not till emergence from the aphid mummy.…”
Section: Chemoreceptors On the Antennaecontrasting
confidence: 96%
“…However, older larvae did not show this preference and attacked the two species of prey irrespective of the aphids that were previously fed. This is different from what has been shown for parasitoids (van Emden et al 2008 ) where the selectivity for prey can develop late during the larval -pupation phase and even not till emergence from the aphid mummy.…”
Section: Chemoreceptors On the Antennaecontrasting
confidence: 96%
“…Studies on this topic in parasitoids are more advanced; general reviews, such as e.g. Vet and Dicke (1992) , De Bruyne and Baker (2008) , van Emden et al (2008) , Lei and Vickers (2008) and Riffell et al (2008) can provide important insights for coccinellid researchers.…”
Section: Olfactionmentioning
confidence: 99%
“…A. ervi, a generalist aphid parasitoid closely related to A. colemani, showed a flight response to 6-mehtyl-5-hepten-2-one, one component of broad bean volatiles (Du et al, 1998). In addition, van Emden et al (2008) reported that A. colemani, which artificially learned a glucosinolate, showed a preference for Brassica plants. These studies indicate the possibility that key components of plant volatiles are sufficient to help generalist aphid parasitoids recognize their host plants, supporting our hypothesis that aphidinfested borage attracts parasitoids by components common to other aphid-infested plants.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that some generalist parasitoids show a preference for volatiles from plants on which their host aphids have fed by learning volatiles (Gutiérrez-Ibáñez et al, 2007;Villagra et al, 2007;Takemoto et al, 2009). A. colemani experiences plant volatiles on the mummy surface when they emerge, and shows a preference for host plant volatiles (Storeck et al, 2000;van Emden et al, 2008). According to these studies, A. colemani should show a preference for borage volatiles only when they have emerged from aphids feeding on borage; that is to say, if A. colemani shows a preference for borage despite being reared on aphids feeding on other plants, then borage has an attractive odor to A. colemani.…”
Section: Introductionmentioning
confidence: 99%